INFLUENCE OF VARYING RUMEN DEGRADABLE TO UNDEGRADABLE PROTEIN RATIOS ON MILK YIELD, COMPOSITION AND SOME BLOOD PARAMETERS OF KARADI EWES - Jalal Alkass; KAMAL NOMAN DOSKY; EMAD TAYAR SADEEQ BUTI (Mesopotamia Journal of Agriculture)
Twenty-four lactating Karadi ewes, 3-5 years old and 54±0.69 kg in body weight were used to study the effect of RDP to RUP ratio on milk yield, composition and some blood attributes. Ewes with their lambs were placed in individual pens and fed concentrate and straw ad lib. Milk yield was recorded in two successive days at biweekly intervals commencing at 2nd week post lambing by using hand milking and lamb suckling technique. Also, blood samples were withdrawn at start, mid and at the end of the experimental period (84 days). Daily milk yield and total milk yield averaged 1.16±0.038 and 98.31±4.44 kg, respectively. Feeding ewes protected SBM resulted in a non-significant increase in milk yield in T3 (15.22%), and 12.06% in FCM in T2 as compared to control. A significant (P<0.05) effect of treatment on both percentage and yield of fat and protein was observed. However, the highest fat percent and yield was recorded in T2, whereas, the highest percent and yield of protein was noticed in T2 and T3, respectively. Cholesterol and urea levels was significantly (P<0.05) lower in T1 as compared to other groups.